Ranking lean tools for world class reach through grey relational analysis - Satolo, Eduardo Guilherme [UNESP]; Leite, Caroline [UNESP]; Calado, Robisom Damasceno; Goes, Gustavo Antiqueira [UNESP]; Salgado, Douglas D'Alessandro [UNESP] (Emerald Group Publishing Ltd, 2018)
Purpose - The lean production system and world class manufacturing (WCM) have been prominent in recent studies due to their conceptual synergy. However, although the number of studies is increasing, the research is immature, especially regarding the interaction between topics. Therefore, the purpose of this paper is to rank the tools of the lean production system, indicating how they help organizations achieve WCM, using the theory of grey systems. Design/methodology/approach - Therefore, the authors conducted an initial survey to collect data to determine how the lean production tools are related to the WCM pillars. These data were analyzed by the grey relational analysis statistical method, which passes through the construction of four stages. Findings - The results show that of the lean production tools, stream mapping, kaizen, total productive maintenance, Six Sigma, standardized work and 5S stand out for their use and implementation in the organizational environment and facilitate organizations' transitions to world-class performance through the WCM pillars. Practical implications - The results achieved guide organizations to use the tools of the lean production system to help them reach world class status. Originality/value -This paper stands out in the field of operations management, specifically in the research on lean production, by making use of the theory of grey correlation system in an innovative and original way. In addition, it promotes the consolidation of information on two of the main administrative strategies currently employed in the organizational environment.
Keywords: Survey; Lean manufacturing; Lean tools; Grey relational analysis; World class manufacturing